Menimbang Konstruksi Hukum Kepailitan Bank; Perspektif Nilai-Nilai Dasar Dan Tujuan Hukum - M. Fauzi (Jurnal Risalah Hukum, 2010)
Pasal 2 ayat (3) Undang-undang Nomor 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang determined that bankruptcy may be filed against banks by Bank Indonesia. The request is based solely upon the financial condition and the condition assessment of the overall banking sector. So when the public interest to maintain the credibility of banks and banking stability is determined as a legal benefit to be achieved by appointing the Bank Indonesia as the banking regulatory authority as the only party who can file a bankruptcy petition on the bank, then as the party authorized to file bankruptcy on a bank, Bank Indonesia should continue to protect the rights of the creditor banks with a bank that has filed bankruptcy criteria bankruptcy in order to give justice to the creditor and guaranteeing their rights for the sake of legal certainty, as already stipulated in the Law on Bankruptcy. Because justice and protection of creditor rights is a cornerstone for the realization of justice within the law.